2023
DOI: 10.1021/acs.cgd.2c01269
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Investigation of Benperidol and Droperidol Solid Solutions in Different Crystal Structures

Abstract: We present an experimental and computational study of solid solution formation between structurally highly similar active pharmaceutical ingredients droperidol and benperidol in nonsolvates, dihydrates, and several solvates formed by these compounds. We demonstrate that the formation of solid solutions strongly depends on the crystal structure of the phase. In some of the structures, almost complete replacement of benperidol with droperidol can be achieved, whereas in other structures, the replacement is possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 76 publications
(90 reference statements)
0
6
1
Order By: Relevance
“…In contrast, our previous study 27 show that in case of notably smaller change of the molecular structure, as replacement of benperidol and droperidol molecules, allow use of the energy change as a criterion for prediction of the solid solution formation. Also, additional view on the energy differences were obtained by analysing the interaction energy for molecule pairs for which there are atoms within 3.80 Å radius from the central molecule given in Tables S7 -S18 Supporting Information.…”
Section: Evaluation Of the Weak Intermolecular Interactionscontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast, our previous study 27 show that in case of notably smaller change of the molecular structure, as replacement of benperidol and droperidol molecules, allow use of the energy change as a criterion for prediction of the solid solution formation. Also, additional view on the energy differences were obtained by analysing the interaction energy for molecule pairs for which there are atoms within 3.80 Å radius from the central molecule given in Tables S7 -S18 Supporting Information.…”
Section: Evaluation Of the Weak Intermolecular Interactionscontrasting
confidence: 56%
“…Theoretical calculations were performed for three general sets of crystal structures as in our previous studies 27,40 The second set (Isostructural) was structures in which the functional group of the original molecules were fully replaced by one of the alternative studied functional groups, see Figure 2. The third set (Substituted) was structures for which symmetry was removed, and the functional group was replaced for one of the molecules out of 4 (out of 2 for 2OH5NBA and 8 for 4Me3NBA and 5OH2NBA) in the unit cell, see Figure 2 All three sets of crystal structures were initially geometry optimized in Quantum ESPRESSO 41 by relaxing positions of all atoms and the unit cell parameters (vc-relax), with ultra-soft pseudopotentials 42 from the original pseudopotential library and a 130 Ry plane-wave cut-off energy using PBE 43 functional with vdW interactions treated according to the D3 method of Grimme 44 .…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid solutions have been discovered and their properties and formation explored between structurally highly similar compounds: molecules differing by halogen (and halogen/methyl) substituents; , molecules differing by S/O atoms; , molecules differing by single/double bonds in the carbon atom framework; , and molecules differing by F/H atoms. , However, it has been observed that, in some cases, even very similar molecules are immiscible or only mix in limited composition ranges in the solid state . Therefore, individual case studies on the miscibility of similar organic compounds in the solid state are necessary to uncover the general aspects governing solid solution formation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Molecules with chlorine atoms and methyl groups in equivalent sites are often interchangeable in the crystal structures, 19,20 i.e., the overall structure is not significantly altered. 21 Solid solutions have been discovered and their properties and formation explored between structurally highly similar compounds: molecules differing by halogen (and halogen/ methyl) substituents; 22,23 atoms; 24,25 molecules differing by single/double bonds in the carbon atom framework; 26,27 and molecules differing by F/H atoms. 28,29 However, it has been observed that, in some cases, even very similar molecules are immiscible or only mix in limited composition ranges in the solid state.…”
Section: Introductionmentioning
confidence: 99%